Enhanced Photocatalytic and Photoluminescence Properties Resulting from Type-I Band Alignment in the Zn2 GeO4/g-C3 N4 Nanocomposites - Suzuki, Victor Y.; Amorin, Luis H. C.; Fabris, Guilherme S. L. [UNESP]; Dey, Swayandipta; Sambrano, Julio R. [UNESP]; Cohen, Hagai; Oron, Dan; La Porta, Felipe A. (MDPI, 2022)
Well-defined Zn2 GeO4/g-C3 N4 nanocomposites with a band alignment of type-I were prepared by the ultrasound-assisted solvent method, starting from g-C3 N4 nanosheets and incorporating 0, 10, 20, and 40 wt% of Zn2 GeO4. In this study, we have investigated in-depth the photoluminescence emission and photocatalytic activity of these nanocomposites. Our experimental results showed that an increased mass ratio of Zn2 GeO4 to g-C3 N4 can significantly improve their photoluminescence and photocatalytic responses. Additionally, we have noted that the broadband photoluminescence (PL) emission for these nanocomposites reveals three electronic transitions; the first two well-defined transitions (at ca. 450 nm and 488 nm) can be attributed to π* → lone pair (LP) and π* → π transitions of g-C3 N4, while the single shoulder at ca. 532 nm is due to the oxygen vacancy (Vo) as well as the hybridization of 4s and 4p orbital states in the Zn and Ge belonging to Zn2 GeO4. These experimental findings are also supported by theoretical calculations performed under periodic conditions based on the density functional theory (DFT) fragment. The theoretical findings for these nanocomposites sug-gest a possible strain-induced increase in the Zn-O bond length, as well as a shortening of the Ge-O bond of both tetrahedral [ZnO4] and [GeO4] clusters, respectively. Thus, this disordered structure promotes local polarization and a charge gradient in the Zn2 GeO4/g-C3 N4 interface that enable an efficient separation and transfer of the photoexcited charges. Finally, theoretical results show a good correlation with our experimental data.
Keywords: band alignment; DFT calculations; g-C3 N4/Zn2 GeO4; nanocomposites; optical and photocatalytic properties